Novel curcumin-loaded human serum albumin nanoparticles surface functionalized with folate: characterization and in vitro/vivo evaluation - Song Z; Lu Y; Zhang X; Wang H; Han J; Dong C (Dove Medical Press, 2016)
Zhiwang Song,1,* Yonglin Lu,1,* Xia Zhang,1,* Haiping Wang,2 Junyi Han,3 Chunyan Dong1 1Breast Cancer Center, 2Department of Pharmacy, 3Department of Gastrointestinal Surgery, Shanghai East Hospital, Tongji University, Shanghai, People’s Republic of China *These authors contributed equally to this work Abstract: Folate-conjugated, curcumin-loaded human serum albumin nanoparticles (F-CM-HSANPs) were obtained by the chemical conjugation of folate to the surface of the curcumin (CM)-loaded human serum albumin nanoparticles (NPs). The NPs were characterized by various parameters, including size, polydispersity, zeta potential, morphology, encapsulation efficiency, and drug release profile. The mean particle size of F-CM-HSANPs was 165.6±15.7 nm (polydispersity index <0.28), and the average encapsulation efficiency percentage and drug loading percentage of the F-CM-HSANPs were 88.7%±4.8% and 7.9%±0.4%, respectively. Applied in vitro, the CM NPs, after conjugation with folate, maintained sustained release, and a faster release of CM was more visibly observed than the unconjugated NPs. F-CM-HSANPs can prolong the retention time of CM significantly in vivo. However, after intravenous injection of F-CM-HSANPs, the pharmacokinetic parameters of CM were not significantly different from those of CM-loaded human serum albumin NPs. The improved antitumor activity of F-CM-HSANPs may be attributable to the protection of drug from enzymatic deactivation followed by the selective localization at the desired site. These results suggest that the intravenous injection of F-CM-HSANPs is likely to have an advantage in the current clinical CM formulation, because it does not require the use of a solubilization agent and it is better able to target the tumor tissue. Keywords: curcumin, folate, HSA nanoparticles, pharmacokinetic parameters